2021
DOI: 10.1007/s00192-021-04782-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of genetic association studies of pelvic organ prolapse

Abstract: Introduction and hypothesis Family and twin studies demonstrate that pelvic organ prolapse (POP) is heritable, but the genetic etiology is poorly understood. This review aimed to identify genetic loci and specific polymorphisms associated with POP, while assessing the strength, consistency, and risk of bias among reported associations. Methods Updating an earlier systematic review, PubMed and HuGE Navigator as well as relevant conference abstracts were sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…The genetic contributions to POP remain poorly understood. Additional work needs to be done to provide further validation of POP predisposition variants in a variety of different populations to establish the role of these genes in the pathogenesis of prolapse [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genetic contributions to POP remain poorly understood. Additional work needs to be done to provide further validation of POP predisposition variants in a variety of different populations to establish the role of these genes in the pathogenesis of prolapse [5].…”
Section: Discussionmentioning
confidence: 99%
“…Previous genetic analyses have revealed candidate genes associated with POP. These genes included collagen type I alpha (COL1A1) [4,5], collagen type III alpha 1 (COL3A1) [6], laminin gamma-1 (LAMC1) [7], and matrix metalloproteinases (MMPs) [8], which are all enrolled in extracellular matrix (ECM) pathways. The latest review comprehensively summarized and identified genetic polymorphisms associated with POP, including steroid hormone receptor genes and collagen/elastic fiber synthesis genes [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion confirmed both genetic and environmental influences on POP. Previous and recent genome-wide association studies, linkage studies, and candidate gene association studies have identified single nucleotide polymorphisms (SNPs) in genes mainly implicated in extracellular matrix organization and disassembly, and steroid hormone receptor genes, [7][8][9][10][11] suggesting a role of pelvic floor supportive tissue trauma and hormone exposure in the pathogenesis of POP. However, few validated loci exist from these studies.…”
mentioning
confidence: 99%
“…Large population-, family-and twins-based studies have confirmed a genetic risk factor. This fascinating systematic review and meta-analysis by Allen-Brady et al [1], is aimed at identifying the genetic loci and specific polymorphisms associated with POP, while assessing the strength, consistency and risk of bias amongst reported associations. It is important because the genetic contribution to POP is poorly understood whereas there is string evidence of heritability for POP.…”
mentioning
confidence: 99%